Analisis Implementasi Manajemen Kepemimpinan Pendidikan Anak Usia Dini di Taman Kanak-Kanak Kabupaten Cikarang Selatan - Abdy Chairul Kurniawan; Azi Matur Rahmi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Based on the preliminary study, the researcher sees the problem that early childhood education institutions still have difficulties in designing and implementing leadership management that is in accordance with early childhood education standards but basically leadership cannot be separated from the professionalism of the teaching staff so that teaching and learning activities continue according to the child's level of development early age. Judging from the lack of optimal institutional leadership management in compiling and leadership in coordinating leadership, it can be seen from the duties of institutional leaders, learning approaches, and approaches to the nature of work of managers in leading. Based on this, researchers will conduct research on the Analysis of the Implementation of Early Childhood Leadership Management in Kindergartens in South Cikarang Regency. This type of research is mixed research using a quantitative approach. This study uses a mixed method "Explanatory mixed Methods design", namely quantitative and qualitative research methods sequentially. The results of this study are seen from the preparation of personnel, motivation and communication.